2013
DOI: 10.1371/journal.ppat.1003569
|View full text |Cite
|
Sign up to set email alerts
|

The sst1 Resistance Locus Regulates Evasion of Type I Interferon Signaling by Chlamydia pneumoniae as a Disease Tolerance Mechanism

Abstract: The sst1, “supersusceptibility to tuberculosis,” locus has previously been shown to be a genetic determinant of host resistance to infection with the intracellular pathogen, Mycobacterium tuberculosis. Chlamydia pneumoniae is an obligate intracellular bacterium associated with community acquired pneumonia, and chronic infection with C. pneumoniae has been linked to asthma and atherosclerosis. C. pneumoniae is a highly adapted pathogen that can productively infect macrophages and inhibit host cell apoptosis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Both of the independent lines of Sp140 -/were similarly susceptible to M. tuberculosis ( Figure S2E). Previous reports have shown that in addition to M. tuberculosis, the Sst1 locus also controls responses against other intracellular bacterial pathogens such as L. monocytogenes and C. pneumoniae (Boyartchuk et al, 2004;He et al, 2013;Pichugin et al, 2009). Therefore we infected Sp140 -/and B6.Sst1 S mice with L. monocytogenes.…”
Section: Sp140mentioning
confidence: 99%
“…Both of the independent lines of Sp140 -/were similarly susceptible to M. tuberculosis ( Figure S2E). Previous reports have shown that in addition to M. tuberculosis, the Sst1 locus also controls responses against other intracellular bacterial pathogens such as L. monocytogenes and C. pneumoniae (Boyartchuk et al, 2004;He et al, 2013;Pichugin et al, 2009). Therefore we infected Sp140 -/and B6.Sst1 S mice with L. monocytogenes.…”
Section: Sp140mentioning
confidence: 99%
“…Previously we reported that B6-sst1S mice infected with Chlamydia pneumoniae, as well as their bone marrow-derived macrophages (BMDMs) infected with C.pneumoniae, produce higher levels of IFNb 16 . This was associated with increased death of infected macrophages in vitro, which could be reduced using IFN receptor (IFNAR1) blocking antibodies.…”
Section: Tnf Triggers Hyperactivity Of Type I Interferon (Ifn-i) and mentioning
confidence: 99%
“…Subsequent experiments using the sst1 congenic mice revealed that the sst1 locus controlled macrophage interactions with Mtb and other intracellular bacterial pathogens -Listeria monocytogenes 15 and Chlamydia pneumonia 16 . Using positional cloning approach, we have identified a variant of the interferon-inducible nuclear protein Sp110 or Ipr1 (intracellular pathogen resistance 1), as a strong candidate gene, whose expression is completely abolished in sst1S macrophages 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experiments using the sst1 congenic mice revealed that the sst1 locus controlled macrophage interactions with Mtb and other intracellular bacterial pathogens -Listeria monocytogenes [18] and Chlamydia pneumonia [19]. Using positional cloning approach, we have identified a variant of the interferon-inducible nuclear protein Sp110, Ipr1 (intracellular pathogen resistance 1), as a strong candidate gene, whose expression is completely abolished in sst1S macrophages [20].…”
Section: Introductionmentioning
confidence: 99%